Autotransplantation of Two Immature Third Molars with the Use of L-PRF - Manon Rey Lescure; Nicola Alberto Valente; Sibylle Chatelain; Chiara Cinquini; Antonio Barone (Hindawi Limited, 2021)
Tooth autotransplantation is a procedure which provides the extraction of an erupted or impacted tooth and its repositioning to another site in the oral cavity. This Case Report describes a successful case of two autotransplantations of open-apex mandibular third molars in place of the hopeless first mandibular molars with the use of L-PRF in a growing patient. A 15-year-old male patient was referred to the Dental Clinic for the extractions of the two hopeless mandibular first molars. Autotransplantation was considered the best treatment option for both sites 36 and 46, because the presence of two impacted mandibular third molars (38 and 48) with an incomplete root formation. Teeth 36 and 46 were extracted and replaced with teeth 38 and 48. The patient had an uneventful healing. At follow-up visits, the two autotransplanted teeth showed physiologic mobility, absence of inflammation and discomfort, and absence of infection; probing depth values were within normal range, and the vitality tests were positive. After 2 years, the teeth in position 36 and 46 showed absence of infection and mobility, and positive pulp vitality tests and the radiographic examinations exhibited closure of the root apices as well as absence of any periapical radiolucency or root resorption. Tooth autotransplantation is a good treatment option in case of tooth loss offering an alternative to traditional or implant-supported prosthesis especially for growing patients.